Electronics System Design Techniques for Safety Critical Applications - Sterpone, Luca (Lecture Notes in Electrical Engineering, 2009)
Nowadays, electronic systems are increasingly used in safety critical applications compared to two decades ago. Electronic devices are being used in applications where their correct operation is vital to ensure the safety of the human life and the environment. These applications ranging from the anti-lock braking systems in automobiles, to the fly-by-wire aircrafts, to biomedical supports to the human care. It is, therefore, vital that electronic designers be aware the safety implications of the systems they develop. This book attacks SRAM-based Field Programmable Gate Array, as the most widely used reconfigurable devices, from a new perspective. It provides a series of new algorithms and techniques for the evaluation and the increase of the dependability when faulty effects such as Single Event Upsets (SEUs) of Soft-Errors (SEs) are considered. Particular relevance is given to the radiation phenomena concerning both the physical and the architectural design. The innovation of the analysis and the design flows proposed in this manuscript are a milestone of a complete design methodology solving the industrial designer's needs for implementing SAFE electronic systems using SRAM-based FPGAs in critical environments, in particular the space or avionics ones. Electronics System Design Techniques for Safety Critical Applications gives an investigating overview on side-devices such as Reconfigurable Compute Fabric and depicts the advantages and constraints of the reconfigurable computing based on FPGA for multimedia applications and biomedical applications.